2016
DOI: 10.1002/evan.21498
|View full text |Cite
|
Sign up to set email alerts
|

Digestive enzymes of human and nonhuman primates

Abstract: All living organisms need to consume nutrients to grow, survive, and reproduce, making the successful acquisition of food resources a powerful selective pressure. However, acquiring food is only part of the challenge. While all animals spend much of their daily activity budget hunting, searching for, or otherwise procuring food, a large part of what is involved in overall nutrition occurs once the meal has been swallowed. Most nutritional components are too complex for immediate use and must be broken down int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 118 publications
(382 reference statements)
0
57
0
Order By: Relevance
“…We also did not find an effect of the percentage of feeding and foraging time spent consuming invertebrates measured at the group level on overall gut microbial community structure. This may be due to the fact that invertebrate prey eaten by capuchins do not generally contain indigestible compounds, other than chitin, and capuchins are known to have active endogenous chitinases (Janiak, ; Raubenheimer & Rothman, ; Stevens & Hume, ). It also may be attributed to fact that diet measured at such a broad scale (e.g., lumping all fruit species into a single category and all invertebrate taxa into a single category) does not predict changes in the gut microbiome, or that percent time spent feeding and foraging is not a strong measure of amount of food consumed or the amount of specific nutrients ingested (Garber, Righini, & Kowalewski, ).…”
Section: Discussionmentioning
confidence: 99%
“…We also did not find an effect of the percentage of feeding and foraging time spent consuming invertebrates measured at the group level on overall gut microbial community structure. This may be due to the fact that invertebrate prey eaten by capuchins do not generally contain indigestible compounds, other than chitin, and capuchins are known to have active endogenous chitinases (Janiak, ; Raubenheimer & Rothman, ; Stevens & Hume, ). It also may be attributed to fact that diet measured at such a broad scale (e.g., lumping all fruit species into a single category and all invertebrate taxa into a single category) does not predict changes in the gut microbiome, or that percent time spent feeding and foraging is not a strong measure of amount of food consumed or the amount of specific nutrients ingested (Garber, Righini, & Kowalewski, ).…”
Section: Discussionmentioning
confidence: 99%
“…Pancreatic enzyme secretions subsequently are intended to finish the process of disintegration and dissolution of foodstuffs (3,18,27). Different digestive enzymes have distinctive functions such as proteases and peptidases that disintegrate proteins into small peptides and amino acids; lipases break down fats into fatty acids and glycerol; amylases disintegrate complex carbohydrates into glucose and other monosaccharides; and nucleases break down nucleic acids into nucleotides (1,10,13,14,(24)(25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…Fermentation simultaneously produces large quantities of bacterial RNA which must be metabolized for energy by the host's RNASE enzyme. In most mammals, the RNASE enzyme, encoded by the gene RNASE1 encodes, operates optimally at pH 7.4–7.8 . Using experimental protein assays, researchers found that amino acid changes in a colobine‐specific duplication of the RNASE1 gene, RNASE1B , lowered the optimal pH for enzymatic activity to 6.4–6.6, matching the colobine small intestine environment .…”
Section: Functional Genomics and Evolutionary Anthropologymentioning
confidence: 99%